Development and validation of the scale of psychological responses of grief before the loss of health (RPD-PS-38) - Miaja Ávila, Melina; Moral de la Rubia, José (Psicooncología, 2014)
Background: A qualitative study proposed a scale to assess the 5 phases of grief before the loss of health, the FD-66 scale. Another quantitative study contrasted the Kübler-Ross model in which the FD-66 scale is based. This quantitative study defined each phase of grief by means of one-factor scales, using 39 of 66 items composing the FD-66 scale, refuted the Kübler-Ross sequential model, and suggested contrasting a correlated 6-factors model (including 4 items ignored in the analysis).Objectives: 1) to determine the factor structure of the FD-66 scale reduced to 43 items, 2) calculate the internal consistency of the factors, 3) describe the shape of the distribution of the factors, 4) describe the frequency of expression of grief responses, and 5) calculate and compare the means of the factors. Method: The FD-66 scale was applied to a non-probability sample of 120 Mexican women with cancer. Results: The scale was reduced to 38 items, presented a structure of correlated six first-order factors (denial, anger, promises/negotiation, faith/hope, depression, and acceptance), and independent two second-order factors (negative affect reaction, and positive attitude toward disease). These factor models were consistent with the hypothesis. The internal consistency of the factors was high and its distributions were not adjusted to normal curve. The most frequent psychological responses were faith/hope and acceptance; lest frequent responses were anger, depression and denial; and intermediate one was promises/ negotiation. Conclusions: The scale of Psychological Responses of Grief before Loss of Health (RPDPDS- 38) is reliable and valid. Use and study is recommended.
Keywords: Grief; cancer; denial; anger; bargaining; depression; acceptance.